The measurement model of social responsibility construct from an Islamic perspective: empirical analysis of Malaysian business organizations - Mohammed Kamil, Naail; Sulaiman, Mohamed; Osman-Gani, Aahad M.; Mohd. Israil, Khaliq Ahmad (The Journal of Knowledge Economy and Knowledge Mangement, 2012)
The present study investigates the measurement model of the Islamic social responsibility (ISR) construct in business organizations in the Malaysian context. The study aims to contribute new knowledge to the existing literature of Social responsibility (SR) in general, and ISR in particular. Using disproportionate stratified random sampling, the survey data used for this empirical research was drawn from 405 Muslim employees in business organizations in Malaysia. After yielding an instrument to measure ISR, Principal Component Analysis (PCA) using SPSS version 18.0, and Confirmatory Factor Analysis (CFA) using AMOS version 18.0 were conducted. Good fit indices from CFA revealed that, the ISR measurement model in the Malaysian business organizational context is explained by five components; Integrity, Emotional Control, Fulfillment of Covenant, Justice and Truthfulness. Theoretical and practical implications from the study were further discussed. Human Resource Development professionals, organizational managers and government authorities may use the findings of this study to justify their efforts in designing appropriate learning and performance improvement interventions so that ISR of employees can be monitored and further enhanced.